A comprehensive design methodology of organic Rankine cycles for the waste heat recovery of automotive heavy-duty diesel engines. (5th August 2015) - Amicabile, Simone; Lee, Jeong-Ik; Kum, Dongsuk
Abstract: One of the most promising approaches to recover the waste heat from internal combustion engines is the Organic Rankine Cycle owing to its efficiency and reliability. The design optimization of ORC, however, is nontrivial because there exist many design variables and practical considerations. The present paper proposes a comprehensive design methodology to optimize the Organic Rankine Cycles (ORC) considering a wide range of design variables as well as practical aspects such as component limitations and costs. The design process is comprised of three steps: heat source selection, candidate fluid selection, and thermodynamic cycle optimization. In order to select the best waste heat source, the available energy and other practical considerations of various heat sources have been compared. Among others, the Exhaust Gas Recirculation (EGR) cooler is found to be the best heat source, and thus used for the rest of this study. Based on a systematic working fluid analysis, Ethanol, Pentane, and R245fa are selected as three candidate fluids. For the comprehensive ORC optimization, four types of cycle layouts are considered; 1) subcritical cycle without a recuperator, 2) subcritical cycle with a recuperator, 3) supercritical without a recuperator, and 4) supercritical cycle with a recuperator. Four cycle layouts coupled with three candidate fluids give a total of twelve cycle analyses. Results show that the best performance is provided by the regenerative subcritical cycle with Ethanol, while the solution with minimum capital cost is the subcritical cycles with Ethanol but without a recuperator. Highlights: Selection of the best waste heat source of a diesel engine for a heat recovery system. Screening process to identify the most suitable working fluids for the system. Comprehensive ORC optimization is introduced for four types of cycle layouts. Pay Back Time investigation to present the economic analysis of the cycles.